Liberalisme dalam Islam Menurut Tafsir Maudhu‘i - Muhammad Rifky Maulana; Muhammad Rijalul Fikri; Muftillahi Adillah Salsabila Assadiyyah (Melati Institute, 2023)
Liberalism in Indonesia is often highlighted by state elements and Indonesian intellectuals. Therefore religious values must be maintained and applied in life so that there can be a balance between moral and ethical values of individual freedom or liberalism itself. This study aims to describe the essence of liberalism from an Islamic point of view, and become reference material as well as studies that are worth reading. This research uses the maudu'i (thematic) method which is entirely a qualitative research. The sources of reference used in this study are various, including sources from printed and digital documents, both in the form of books, books, journals, essays, and other relevant references. The results of the research show that Islam and liberalism have different beliefs and values in viewing life and society. Liberalism is often seen as contrary to the moral and ethical values espoused by Islam, because it prioritizes individual freedom without considering the impact on society and the environment. However, Islam also gives individual freedom to choose and determine their own way of life, as long as it does not conflict with religious teachings. The idea of liberalism was introduced to Islam through several approaches, namely: the spread of religious pluralism, the relativism of truth, and the reinterpretation of the Koran and religious teachings. In the Qur'an itself there are several verses that discuss liberalism and its derivations.